COVID-19 vaccination refusal among the anti-vaccinationists in a Chinese society: a critical medical anthropology study of the vaccination barriers - Siu, Judy Yuen-Man (Frontiers in Public Health, 2025)
IntroductionThis study investigated the reasons for COVID-19 vaccination refusal among some Hong Kong residents who were anti-vaccinationists, despite the implementation of a vaccine incentive policy called the Vaccine Pass. The health belief model and the theory of planned behavior have been widely employed to analyze the determinants of COVID-19 vaccination. However, these two theories focus on the micro individual factors, which do not provide a sufficiently comprehensive analysis.Study designA qualitative descriptive approach with a critical medical anthropology framework.MethodsThis study adopts a critical medical anthropology framework that provides a micro and macro analysis at four social levels. A qualitative approach with individual, semi-structured, in-depth interviews was conducted from September 2022 to March 2023 with 30 individuals aged 20–59 years who did not receive COVID-19 vaccination in Hong Kong. The participants were recruited through purposive sampling and snowball sampling. A thematic analysis of data was implemented.ResultsThe reasons for COVID-19 vaccination refusal involved intertwining relationships among factors in the four social levels of the critical medical anthropology framework. The participants’ doubts about the safety of COVID-19 vaccines at the individual level were interacting with: (1) their ethnocultural beliefs and the perceived profit-oriented nature of vaccine production and distribution at the macro-social level, (2) their interpretation of the inconsistent advice of medical doctors at the micro-social level, and (3) their distrust in the government’s vaccination policies at the intermediate-social level.ConclusionThe participants’ refusal of COVID-19 vaccines was correlated with perceived profit motives related to the vaccine, perceived conflict of interest of health-care providers, and the distrust of government.